Effect of active triangle and quartangle passing training on the accuracy of passing of men's participants futsal extracurricular - Danang Afrianto; Pipit Fitria Yulianto; Wisnu Mahardika; Ronny Suryo Narbito (Fair Play, 2024)
This study aims to determine the effect of active triangle passing and active rectangular passing training methods on the passing accuracy of men's futsal extracurricular participants at SMA Negeri 6 Surakarta. The type of research used in this research is an experiment using the research design "The Two Group Pretest Post-test Design" namely an experimental research design carried out on two different groups who received different training or treatment. The research sample consisted of 30 people.The instrument that will be used is a soccer playing skills test. Hypothesis testing uses the t-test with the help of the SPSS 25 program, namely by comparing the mean between group 1 (pretest) and group 2 (post-test). Hypothesis test results for active triangle passing training methodshows a difference in mean value of 2.13 with a percentage of 31% and resultstestt, obtained t count > t table = 6.52 > 2.145. Meanwhile, the results of the hypothesis test for the rectangular passing practice method showed a difference in mean value of 2.86 with a percentage increase of 41.26% and the resultst valuecount > t table = 9.28 > 2.145. So it can be concluded that Ha is accepted, which means that the triangle active passing training method and the rectangular active passing training method havesignificant influenceon increasing the passing accuracy of men's futsal extracurricular participants at SMA Negeri 6 Surakarta